Analisis Kesiapan Sertifikasi Chse (Cleanliness, Health, Safety, Environtment) Pada Cafe Sawah Desa Pujon Kabupaten Malang - Ferra Eka Ramadhani,; Ninda Rachmawati, (JURNAL EKONOMI, KEUANGAN, PERBANKAN, KEWIRAUSAHAAN DAN KOPERASI, 2022)
In light of the pandemic scenario, tourist attraction management must adopt the Health Protocol by the Guidelines for implementing Hygiene, Health, Safety, and Environmental Preservation in Tourist Attractions. For example, Cafe Sawah, one of Malang's tourist attractions, is frequented by both visitors and locals. The goal of this research is to determine the application of sanitation (managers), hygiene (tourists), and occupational health and safety guidelines in the new normal era of COVID-19 as a way to resume operational activities, as well as to identify and analyze the driving and inhibiting factors for CHSE implementation. The study took a qualitative approach, with data gathered through interviews and other sources such as archives and scientific references. According to the findings of this investigation, the manager of Cafe Sawah has followed the appropriate health protocol standards, such as providing closed trash cans and waste management. This conforms with the Ministry of Tourism and Creative Economy requirements for improving the health sector, particularly public health. Furthermore, it is required to wear masks, wash hands often with soap, use hand sanitizer, and remain at a safe distance. Line officers are in charge of control. In compliance with Occupational Health indicators, occupational health kits are supplied for each attraction at tourist locations.